REPRESENTATION OF AFFIX IN THE NOVEL KONSPIRASI ALAM SEMESTA (KOLASE) BY FIERSA BESARI - Nelis Pradesa; Ulinsa Ulinsa; Nur Mustaria Putri (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Representation of Affix in the Novel Konspirasi Alam Semesta (KOLASE) By Fiersa Besari. Problems in this research are (1) how the representation of affix in the novel Konspirasi Alam Semesta by Fiersa Besari. (2) What is the function of affix in the novel  Konspirasi Alam Semesta by Fiersa Besari. This research aimed to (1) to reveal the representation of affix in the novel Konspirasi Alam Semesta by Fiersa Besari. (2) to reveal the function of affix in the novel Konspirasi Alam Semesta by Fiersa Besari. This research is descriptive qualitative research. Data resource in this research is a novel Konspirasi Alam Semesta by Fiersa Besari. Data collecting technique used in this research is literature research technique or sequence activities related on references data collection, reading and write down the written data sources in accordance with the problem. The result conducted in this research are 1) affix in the novel Konspirasi Alam Semesta. Word formation occurs by attaching a prefix at the beginning of the root word, attaching an infix in the middle of the root word, attaching of suffix at the end of the root word, and attaching a confix or simulfix simutaneously at the beginning and at the end of the basic form. The function of affix in the novel Konspirasi Alam Semesta. There are 12 function of affix in the novel Konspirasi Alam Semesta by Fiersa Besari